Utilization of Different Concentration Sugarcane Molasses to the Quality of Goat Feces-Chicken Excreta-Coconut Husk Organic Liquid Fertilizer - Dwi Ahmad Priyadi; Sefri Toni; Ari Istanti (Faculty of Animal Science, Universitas Gadjah Mada, 2023)
Indonesia is an agricultural country that certainly has the potential for agricultural waste and by-products. Some of those in Indonesia are livestock manure, coconut husk, and sugarcane molasses. Utilization of this waste is limited, which is causing various environmental problems such as environmental pollution. The study is aimed to determine the quality of organic liquid fertilizer made by raw material from goat feces-chicken excreta-coconut husk with various sugarcane molasses concentrations (P0= 0%; P1= 5%; P3= 15%; P4= 20%; P5= 25%). The fermentation was carried out anaerobically for 21 days. The parameters of temperature, pH, organoleptic (color and odor), levels of C-organic, nitrogen (N) total, phosphorus (P) total, potassium (K) total, and biological tests were observed. Biological tests were conducted in the growth of mung bean (Vigna radiata) and spinach (Amaranthus tricolor). Data were analyzed using one-way ANOVA. Variations in the addition of molasses sugarcane did not affect the liquid fertilizer's temperature and pH during fermentation. However, the treatments had positive effect on organoleptic test, C-organic, N total, P total, K total, and biological tests. The addition of 15% sugarcane molasses (P3) showed a dominating performance toward most of the parameters tested. The P3 treatment produced liquid fertilizer with a pleasant smell, and the contents of C-organic, total N, total P, and total K were 2.12%, 0.25%, 0.13%, and 0.13%, respectively. and produce spinach as a biological test with plant height, number of leaves, leaf width, stem diameter, and root length were 21.82 cm, 6.66 sheets, 3.59 cm, 4.09 mm, and 14.67 cm, respectively.